2019
DOI: 10.1249/jes.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

Improving Trip- and Slip-Resisting Skills in Older People: Perturbation Dose Matters

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 50 publications
4
65
0
Order By: Relevance
“…Third, it remains unclear whether the training dosage needed to elicit reactive balance improvements that are both lasting and transferrable to daily life differs between slipping and tripping, or between training modalities (e.g. with our without a treadmill) [49]. Fourth, training interference, which can occur when two trained tasks have conflicting requirements [50], may require more training when PBT targets both slipping and tripping to achieve equivalent improvements when targeting slipping or tripping.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it remains unclear whether the training dosage needed to elicit reactive balance improvements that are both lasting and transferrable to daily life differs between slipping and tripping, or between training modalities (e.g. with our without a treadmill) [49]. Fourth, training interference, which can occur when two trained tasks have conflicting requirements [50], may require more training when PBT targets both slipping and tripping to achieve equivalent improvements when targeting slipping or tripping.…”
Section: Discussionmentioning
confidence: 99%
“…The improved retention of immediate performance gains at 6 months for the higher-dosage group might suggest that the greater number of exposures (two thirds more) could suffice and might be required to consolidate motor memory for later retrieval. Moreover, Karamanidis et al 11 reviewed the practice-dose-response relationship by applying perturbation training during gait based on the recent data in older adults. They reported that a lower-practice dosage might limit the longer-term changes in balance responses, which are generalizable to real daily life perturbation (eg, slip and trip) situations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that overground slip training induced by a vinyl floor and a low-friction movable platform can significantly reduce the rate of falls within the first several trials through immediate (ie, <5 min) improvements in COM state stability via the process of motor adaptation. [10][11][12] Moreover, the improvements in COM state stability (more anterior relative COM position and greater relative COM velocity), vertical limb support (net extensor force), and fall incidence (lower rate of falls) obtained from a single session of 24 overground induced slips were retained for 12 months. 13 Overground slip training has also been shown to possibly transfer/generalize to real-life situations in order to reduce annual falls by 50% in community-dwelling older adults.…”
mentioning
confidence: 99%
“…However, this assumes that adaptations in reactive balance control can be successfully achieved and retained over time. Our group has recently proposed the hypothesis that people with neurological disorders whose sensory input or motor control is affected may have a decreased responsiveness to repeated gait perturbations and that more perturbation trials will be needed to stimulate these adaptations, reflecting a rightward shift in the PBT doseresponse relationship (Karamanidis et al, 2019). In turn, the retention and generalizability of these adaptations may be negatively affected in people with neurological disorders, limiting the overall effectiveness of PBT for falls prevention (Karamanidis et al, 2019).…”
Section: 42: Neurological Diseasementioning
confidence: 99%
“…Our group has recently proposed the hypothesis that people with neurological disorders whose sensory input or motor control is affected may have a decreased responsiveness to repeated gait perturbations and that more perturbation trials will be needed to stimulate these adaptations, reflecting a rightward shift in the PBT doseresponse relationship (Karamanidis et al, 2019). In turn, the retention and generalizability of these adaptations may be negatively affected in people with neurological disorders, limiting the overall effectiveness of PBT for falls prevention (Karamanidis et al, 2019). It remains an area for future research to experimentally investigate the perturbation dose-response relationship in these patient populations, as well as the underlying neurological factors involved in gait adaptation, which should provide more insight into the potential for PBT to reduce falls in these groups.…”
Section: 42: Neurological Diseasementioning
confidence: 99%